ChemInform Abstract: One‐Pot Copper‐Catalyzed Aerobic Decarboxylative Coupling of Phenylacetic Acids with o‐Aminobenzenes and Dioxygen as the Oxidant Leading to Benzoxazoles and Benzothiazoles. Issue 11 (March 2015) - Yang, Daoshan; Yan, Kelu; Wei, Wei; Tian, Laijin; Shuai, Yuanyuan; Li, Ruixia; You, Jinmao; Wang, Hua
Abstract A simple procedure is elaborated for the synthesis of benzoxazoles (III) and benzothiazoles (V) by aerobic decarboxylative coupling of phenylacetic acids (II) with corresponding o‐aminobenzenes.